The Relationship between Self-Discrepancy and Depression in Early Adulthood: The Mediating Effects of Self-Absorption and Abstract-Concrete Repetitive Thinking - Sung-Hee Hong; Kyung-Wha Min (Korean Association of Rational Emotive and Cognitive Behavior Therapy, 2026)
This study aimed to examine the mediating effects of self-absorption, abstract-analytical rumination, and concrete-experiential rumination in the relationship between self-discrepancy and depression during early adulthood. For this purpose, a survey was conducted with 375 adults aged 17 to 40, utilizing the Self-Discrepancy Questionnaire, the Scale for Dispositional Self-Focused Attention (SDSDAS), the Repetitive Thinking Mode Questionnaire (RTMQ), and the Integrated Korean version of the Center for Epidemiologic Studies Depression Scale (CES-D), with data subsequently analyzed using SPSS Process Macro 4.2. The key findings are as follows: First, higher levels of self-discrepancy were associated with higher levels of self-absorption, abstract-analytical rumination, and depression, whereas they were associated with lower levels of concrete-experiential rumination. Second, self-absorption, abstract-analytical rumination, and concrete-experiential rumination each showed significant partial mediating effects in the relationship between self-discrepancy and depression. Third, while a sequential mediating effect of self-absorption and abstract-analytical rumination was significant, concrete-experiential rumination was found to function only as a simple mediator without operating through self-absorption. This study provides an integrated understanding of the cognitive content and processes that explain depression in early adulthood and holds significance by specifying the cognitive process linking self-discrepancy and depression as a process of emotional awareness and cognitive processing.